Highly water-absorbent resin and method for producing same

By adjusting the internal and surface crosslinking density of the high-water absorbing resin, a high-water absorbing resin can simultaneously improve the centrifugal separation water retention ability, pressure absorption capacity and absorption speed are prepared, which solves the problem of unbalanced performance in the prior art and achieves the effect of rapid absorption and liquid retention.

JP2025503194AActive Publication Date: 2025-01-30LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024544508
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-03
Filing Date
2023-11-06
Publication Date
2025-01-30
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

When the existing high-water absorption resins improve pressure absorption capacity, it is easy to reduce the centrifugal water retention capacity and absorption speed, and it is difficult to improve the performance of the three at the same time.

Method used

By adjusting the internal crosslinking density and surface crosslinking density, a high water absorption resin is prepared to ensure the balance of its centrifugal water retention ability, pressure absorption capacity and absorption speed, and surface crosslinking is carried out using a specific method to improve performance.

Benefits of technology

It realizes that high water-absorbing resin can be quickly absorbed and maintained after absorbing liquid, and is not easy to leak. It has excellent centrifugal water retention ability and pressure absorption ability, and has a fast absorption speed. It is suitable for sanitary materials such as diapers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503194000001
    Figure 2025503194000001
  • Figure 2025503194000002
    Figure 2025503194000002
  • Figure 2025503194000003
    Figure 2025503194000003
Patent Text Reader

Abstract

The present invention relates to a superabsorbent polymer which has excellent physical properties, such as centrifugal retention capacity, absorbency under pressure, absorption speed, 1-minute tap water absorption capacity, and rewetting characteristics, and which is used in sanitary materials such as diapers, exhibiting high absorption performance and excellent usability, and to a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0159758 dated November 24, 2022 and Korean Patent Application No. 10-2023-0150812 dated November 3, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a highly water-absorbent resin having a high absorption rate, excellent centrifugal water retention capacity and pressure absorption capacity, and excellent rewetting prevention and leakage suppression properties, and a method for producing the same. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric material that can absorb 500 to 1,000 times its own weight in water, and different companies that develop it give it different names, such as SAM (Super Absorbency Material) or AGM (Absorbent Gel Material). Such super absorbent polymers have started to be used in sanitary products, and are now widely used in materials such as soil water retention agents for gardening, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents and poultices in the food distribution field.

[0004] Such superabsorbent polymers are widely used in the field of sanitary materials, such as diapers and sanitary napkins. In the sanitary materials, the superabsorbent polymers are generally contained in a state of being dispersed in the pulp. However, in recent years, efforts have been made to provide sanitary materials, such as diapers, with thinner thicknesses, and as part of these efforts, the development of so-called pulpless diapers, which contain less pulp or even no pulp at all, has been actively promoted.

[0005] To be widely used in such sanitary materials, superabsorbent resins must exhibit high absorption capacity and a fast absorption rate for moisture, and must be able to withstand external pressure without losing absorbed moisture. In addition, they must maintain their shape well even when absorbing water and expanding in volume (swelling), and must exhibit excellent liquid permeability.

[0006] Meanwhile, after a superabsorbent polymer used in a sanitary product absorbs liquid, when pressure is applied due to the weight of the user, some of the liquid absorbed in the superabsorbent polymer may seep out again (rewetting), and urine may leak out (leakage). Therefore, there is a demand for the development of a superabsorbent polymer that can suppress rewetting and leakage.

[0007] However, the absorption speed, the centrifugal water retention capacity, and the pressure absorption capacity are mutually contradictory physical properties, and when high foaming polymerization is performed to increase the absorption speed, the strength of the polymer core is weakened, resulting in a problem of a decrease in the centrifugal water retention capacity and the pressure absorption capacity. In addition, when the crosslink density of the highly water-absorbent resin is increased, the pressure absorption capacity can be improved, but the centrifugal water retention capacity and the absorption speed are decreased, and there is a problem that it is difficult to simultaneously improve physical properties such as the absorption speed, the centrifugal water retention capacity, and the pressure absorption capacity.

[0008] Therefore, there is a demand for the development of a superabsorbent resin that is excellent in both pressurized absorption capacity, centrifugal water retention capacity, and absorption speed, and that can further improve the rewetting prevention properties and leakage suppression properties of sanitary materials such as diapers. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention aims to provide a highly absorbent resin that simultaneously satisfies the required physical properties of centrifugal retention capacity, pressurized absorption capacity, absorption rate, and one-minute tap water absorption capacity, and has rewetting and leakage suppression properties, and a method for producing the same. [Means for solving the problem]

[0010] Therefore, according to one embodiment of the present invention, i) The centrifugal water retention capacity is 30 g / g or more; ii) The effective absorbent capacity (EFFC, 0.3 psi) calculated by the following formula 1 is more than 29.5 g / g; iii) The absorption rate by the vortex method is less than 37 seconds; iv) When 1 g of the superabsorbent polymer is immersed in 2 L of tap water and allowed to swell for 1 minute, the 1-minute tap water absorbency, defined as the weight of water absorbed by the superabsorbent polymer for 1 minute, exceeds 115 g; v) 4 g of a superabsorbent polymer is immersed in 100 g of a 0.9 wt % sodium chloride aqueous solution to swell for 120 minutes, a filter paper is placed on the superabsorbent polymer, and a pressure of 0.75 psi is applied for 5 minutes. The rewetting property (rewetted with pressurized salt water for 2 hours) defined as the weight of water re-exuded from the superabsorbent polymer to the filter paper is less than 3.7 g.

[0011] [Formula 1] Effective Absorbency (EFFC, 0.3 psi) = {Centrifugal Retention Capacity (CRC) + Absorbency Capacity under 0.3 psi Pressure (AUP)} / 2

[0012] According to one embodiment of the present invention, there is provided a method for producing the superabsorbent polymer, comprising the steps of: Providing a monomer composition including an acrylic acid monomer having at least a partially neutralized acid group, an internal crosslinking agent, and a polymerization initiator; cross-linking the monomer composition to form a hydrogel polymer; drying, grinding and classifying the hydrous gel polymer to form a base resin; A surface cross-linking step of forming a surface cross-linked layer on the surface of the base resin in the presence of a surface cross-linking solution containing a surface cross-linking agent, water, and an organic solvent having a boiling point of less than 90° C.; The weight ratio of water / organic solvent in the surface crosslinking solution is 1.0 or more and less than 3.0; The production method is provided, wherein the content of the organic solvent in the surface cross-linking solution is 24% by weight or more. Effect of the Invention

[0013] The highly water-absorbent resin of the present invention is excellent in all physical properties, including centrifugal retention capacity, absorbency under pressure, absorption speed, 1-minute tap water absorption capacity, and rewetting, and is therefore used in sanitary materials such as diapers, and can exhibit not only a fast absorption speed and high absorbency, but also improved rewetting and leakage suppression properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.

[0015] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated and described in detail below, but it is not intended to limit the present invention to the specific disclosed forms, and it should be understood that the present invention includes any modifications, equivalents, or alternatives falling within the spirit and technical scope of the present invention.

[0016] The terminology used herein is for the purpose of referring to particular implementations only and is not intended to be limiting of the invention, and as used herein the singular forms include the plural forms unless the context clearly indicates to the contrary.

[0017] The term "polymer" or "polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include all water content ranges or particle size ranges. Among the above polymers, a polymer in a state after polymerization and before drying and having a water content (water content) of about 40% by weight or more can be called a hydrogel polymer, and particles obtained by crushing and drying such a hydrogel polymer can be called a crosslinked polymer.

[0018] In addition, the term "superabsorbent resin particles" refers to a particulate material that includes an acrylic acid monomer having acidic groups, at least a portion of which has been neutralized, and that includes a crosslinked polymer that has been crosslinked by an internal crosslinking agent.

[0019] In addition, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of the acidic groups being neutralized, or a powder-type base resin consisting of pulverized particles of the crosslinked polymer, depending on the context, or is used to encompass the crosslinked polymer or base resin that has been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Therefore, the term "super absorbent polymer" can be interpreted as including a plurality of super absorbent polymer particles.

[0020] Superabsorbent polymers used in diapers and other sanitary products must exhibit high water absorption capabilities, and must have excellent absorbency under pressure so that absorbed water does not escape even when subjected to external pressure. At the same time, they must also have a high absorption speed so that they can rapidly absorb liquids.

[0021] Therefore, the present invention provides a highly water-absorbent resin excellent in all physical properties, including centrifugal retention capacity, pressure absorption capacity, absorption rate, one-minute tap water absorption capacity, and rewetting properties, and a method for producing the same.

[0022] Specifically, the highly absorbent resin according to one embodiment of the present invention satisfies all of the following physical properties i) to v) and exhibits excellent absorption speed, absorption capacity, rewetting and leakage prevention performance.

[0023] i) The centrifugal water retention capacity is 30 g / g or more; ii) The effective absorbent capacity (EFFC, 0.3 psi) calculated by the following formula 1 is more than 29.5 g / g; iii) The absorption rate by the vortex method is less than 37 seconds; iv) When 1 g of the superabsorbent polymer is immersed in 2 L of tap water and allowed to swell for 1 minute, the 1-minute tap water absorbency, defined as the weight of water absorbed by the superabsorbent polymer for 1 minute, exceeds 115 g; v) 4 g of a superabsorbent resin is immersed in 100 g of a 0.9 wt % sodium chloride aqueous solution to swell for 120 minutes, a filter paper is placed on the superabsorbent resin, and a pressure of 0.75 psi is applied for 5 minutes. The rewetting property (rewetting with pressurized salt water for 2 hours) is defined as the weight of water that seeps out from the superabsorbent resin to the filter paper, and is less than 3.7 g.

[0024] [Formula 1] Effective Absorbency (EFFC, 0.3 psi) = {Centrifugal Retention Capacity (CRC) + Absorbency Capacity under 0.3 psi Pressure (AUP)} / 2

[0025] Generally, superabsorbent resins with high absorption speed by the vortex method are produced by polymerizing monomers in the presence of an internal crosslinking agent and a foaming agent to form a porous structure. However, this method has the problem that the crosslink density is low, resulting in a decrease in centrifugal water retention capacity and pressure absorption capacity.

[0026] Therefore, in order to compensate for the internal crosslink density reduced by the foaming polymerization, a method of increasing the surface crosslink density has been used in the past. However, when the surface crosslinking degree is higher than the internal crosslinking degree, the swelling capacity of the surface of the superabsorbent resin decreases, resulting in a problem of reduced centrifugal water retention. In addition, when the superabsorbent resin swells excessively, the surface crosslinked surface portion breaks, exposing the internal base resin to the outside, which may cause rewetting.

[0027] Therefore, the present inventors have conducted extensive research to provide a superabsorbent resin that simultaneously satisfies physical properties such as centrifugal water retention, EFFC, absorption speed by the vortex method, 1-minute tap water absorption, and rewetting, and as a result, have confirmed that the required physical properties can be simultaneously satisfied by adjusting the internal crosslink density and surface crosslink density of the base resin, thereby completing the present invention. In other words, the superabsorbent resin of the present invention has a small difference between the internal crosslink density and the surface crosslink density of the base resin, so that the surface can expand well when absorbing water, thereby simultaneously improving centrifugal water retention and pressurized absorption, and also exhibiting a high absorption speed.

[0028] The centrifugation retention capacity (CRC) of the superabsorbent resin may be, for example, 30 g / g or more, 31 g / g or more, or 32 g / g or more. The upper limit of the centrifugation retention capacity is not theoretically limited, but may be, for example, 40 g / g or less, 38 g / g or less, or 35 g / g or less.

[0029] The Effective Absorbent Capacity (EFFC) is the arithmetic mean of the Centrifugation Retention Capacity (CRC) and the Absorbent Capacity under Pressure (AUP) at 0.3 psi. In one embodiment of the present invention, the superabsorbent polymer may have an EFFC of more than 29.5 g / g, more than 30 g / g, or more than 30.5 g / g, and not more than 40 g / g, or not more than 38 g / g, or not more than 35 g / g.

[0030] On the other hand, the absorbency under pressure (AUP) of the superabsorbent resin at 0.3 psi can specifically satisfy the range of 25 g / g or more, or 27 g / g or more, or 29 g / g or more, or 30 g / g or more, or 31 g / g or more, and 40 g / g or less, or 38 g / g or less, or 35 g / g or less.

[0031] The absorption speed of the superabsorbent resin by the vortex method satisfies less than 37 seconds, and may satisfy 35 seconds or less, 32 seconds or less, 30 seconds or less, or 29 seconds or less. The faster the absorption speed by the vortex method, the better, and there is no lower limit, but it may be, for example, 10 seconds or more, 15 seconds or more, 20 seconds or more, or 25 seconds or more.

[0032] The one-minute tap water absorption capacity of the superabsorbent polymer may be more than 115 g, more than 125 g, more than 130 g, or 133 g or more, and 200 g or less, 190 g or less, or 180 g or less.

[0033] The tap water used in the measurement of the 1-minute tap water absorbency has an electrical conductivity of 170 to 180 μS / cm. Since the electrical conductivity of tap water has a large effect on the measured physical properties, it is necessary to measure the physical properties using tap water having an equivalent level of electrical conductivity.

[0034] The superabsorbent polymer can satisfy the following: v) 4 g of the superabsorbent polymer is immersed in 100 g of 0.9 wt % sodium chloride aqueous solution to swell for 120 minutes, filter paper is placed on the superabsorbent polymer, and pressure is applied at 0.75 psi for 5 minutes. The rewetting characteristic (pressurized salt water rewetting for 2 hours) defined as the weight of water re-exuded from the superabsorbent polymer to the filter paper is less than 3.7 g. Preferably, the weight of the water may be 3.4 g or less, 3.2 g or less, 3.0 g or less, or 2.7 g or less. The smaller the rewetting amount, the better, and the weight of the water may theoretically be 0 g, for example, 0.1 g or more, 0.2 g or more, or 0.3 g or more.

[0035] The methods for measuring the centrifugal water retention capacity, pressure absorption capacity, absorption rate, one-minute tap water absorption capacity, and rewetting property will be specifically described in the examples described later.

[0036] As described above, the highly water-absorbent resin according to one embodiment of the present invention exhibits high centrifugal water retention capacity, EFFC, and one-minute tap water absorption capacity, and also exhibits a fast absorption rate, and can be suitably used in fields such as sanitary materials, which require high absorption rate along with rewetting and leakage prevention properties.

[0037] On the other hand, the superabsorbent resin is Providing a monomer composition including an acrylic acid monomer having at least a partially neutralized acid group, an internal crosslinking agent, and a polymerization initiator; cross-linking the monomer composition to form a hydrogel polymer; drying, grinding and classifying the hydrous gel polymer to form a base resin; A surface crosslinking step of forming a surface crosslinked layer on the surface of the base resin in the presence of a surface crosslinking solution containing a surface crosslinking agent, water, and an organic solvent having a boiling point of less than 90° C., At this time, the surface crosslinking solution may be prepared by a preparation method in which the weight ratio of water / organic solvent is 1.0 or more and less than 3.0, and the content of the organic solvent in the surface crosslinking solution is 24 wt % or more.

[0038] Hereinafter, each step of the method for producing a superabsorbent polymer will be described in detail with reference to a specific embodiment of the present invention.

[0039] (Step 1) In one embodiment of the production method, step 1 is a step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which is neutralized, an internal crosslinking agent, and a thermal polymerization initiator.

[0040] The acrylic acid monomer is a compound represented by the following Chemical Formula 1.

[0041] [Chemical formula 1] R 1 -COOM 1

[0042] In the above formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0043] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0044] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline material such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree may be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may be precipitated, making it difficult to smoothly carry out polymerization, and conversely, if the neutralization degree is too low, the absorbency of the polymer may be greatly reduced and the polymer may exhibit properties similar to elastic rubber, which is difficult to handle.

[0045] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition including the raw material of the superabsorbent polymer and the solvent, and may be an appropriate concentration taking into consideration the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent polymer is low, which may cause economic problems, and conversely, if the concentration is too high, a part of the monomer may be precipitated, or the crushing efficiency may be low when crushing the polymerized hydrogel polymer, which may cause process problems and may result in a decrease in the physical properties of the superabsorbent polymer.

[0046] In addition, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of the superabsorbent resin particles described later, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in the above step is performed without distinguishing between the surface and the inside, or when a surface crosslinking process of the superabsorbent resin particles described later is performed, the particle surface of the finally produced superabsorbent resin has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.

[0047] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking during polymerization of the acrylic acid-based unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups that can react with the water-soluble substituent of the acrylic acid-based unsaturated monomer and one or more ethylenic unsaturated groups; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by the hydrolysis of the monomer can be used.

[0048] Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene ... Acrylate-based compounds such as acrylate; epoxy-based compounds such as ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, and polyglycerol polyglycidyl ether; triarylamine; propylene glycol; glycerin; or polyfunctional crosslinkers such as ethylene carbonate may be used alone or in combination, but are not limited thereto.

[0049] In the monomer composition, the internal crosslinking agent may be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic acid-based monomer. For example, the internal crosslinking agent may be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention ability.

[0050] In addition, the monomer composition further contains a polymerization initiator for initiating a polymerization reaction of the monomer. Such a polymerization initiator is not particularly limited as long as it is one that is generally used in the production of a highly water-absorbent resin.

[0051] Specifically, the polymerization initiator proceeds by thermal polymerization or photopolymerization. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation with ultraviolet light or the like, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so that both a photopolymerization initiator and a thermal polymerization initiator can be used.

[0052] In one embodiment, the thermal polymerization initiator may be one or more selected from the group consisting of persulfate compounds, azo compounds, hydrogen peroxide, and ascorbic acid. Specifically, examples of the persulfate initiator include sodium persulfate (Na 2 S 2 O 8 ), potassium persulfate (K 2 S 2 O 8 ), Ammonium persulfate ((NH 4 ) 2 S 2 O 8Examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, etc. dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. More various thermal polymerization initiators are described in detail in Odian's book "Principle of Polymerization" (Wiley, 1981), p. 203, and are not limited to the above-mentioned examples.

[0053] More specifically, the thermal polymerization initiator may include the persulfate compound. For example, the thermal polymerization initiator may include sodium persulfate (Na 2 S 2 O 8 ) may also be used.

[0054] The thermal polymerization initiator may be used in an amount of 0.05 to 0.25 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the amount of the thermal polymerization initiator is less than 0.05, the polymerization rate is slowed down and the amount of residual monomer is not reduced because the additional radical initiation reaction with the reducing agent cannot be sufficiently initiated. If the amount of the thermal polymerization initiator is more than 0.25 parts by weight, the amount of water-soluble components is increased, which may cause rewetting of the superabsorbent resin.

[0055] The monomer composition may further include a photopolymerization initiator. The photopolymerization initiator may be any compound capable of forming radicals by light such as ultraviolet light, and may be used without being limited in its structure.

[0056] The photopolymerization initiator may be one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenylgly oxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, as a specific example of acyl phosphine, commercially available lucirin TPO, i.e., diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, may be used. More various photoinitiators are described in detail in "UV Coatings: Basics, Recent Developments and New Application" (Elsevier, 2007), p. 115, by Reinhold Schwalm, and are not limited to the above-mentioned examples.

[0057] The photopolymerization initiator may be used in an amount of 0.001 to 0.010 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the concentration of the photopolymerization initiator is too low, the polymerization rate may be slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.

[0058] The monomer composition may further contain a thickener, a plasticizer, a storage stabilizer, and a reducing agent such as an antioxidant, if necessary.

[0059] The monomer composition including the monomer may be in a solution state dissolved in a solvent such as water, and the solid content in the monomer composition in such a solution state, i.e., the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, may be appropriately adjusted in consideration of the polymerization time and reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80 wt%, or 15 to 60 wt%, or 30 to 50 wt%.

[0060] When the monomer composition has a solid content in the above range, it is advantageous for eliminating the need to remove unreacted monomers after polymerization by utilizing the gel effect phenomenon that occurs in the polymerization reaction of a high concentration aqueous solution, and for controlling the pulverization efficiency when pulverizing the polymer described below.

[0061] In this case, the solvent used is not limited in composition as long as it can dissolve the above-mentioned components, and one or more selected from, for example, water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide may be used in combination.

[0062] (Step 2) Next, a step of cross-linking and polymerizing the monomer composition to produce a hydrogel polymer is carried out.

[0063] The polymerization of the monomer composition is not particularly limited as long as it is a commonly used polymerization method.

[0064] Specifically, polymerization methods are broadly divided into thermal polymerization and photopolymerization depending on the polymerization energy source. Thermal polymerization may be carried out in a reactor having a stirring shaft such as a kneader, and photopolymerization may be carried out in a reactor equipped with a movable conveyor belt. However, the above-mentioned polymerization methods are merely examples, and the present invention is not limited to the above-mentioned polymerization methods.

[0065] For example, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft or by heating the reactor as described above may be several centimeters to several millimeters in size when discharged from the outlet of the reactor depending on the type of the agitator shaft installed in the reactor. Specifically, the size of the obtained hydrogel polymer varies depending on the concentration of the monomer composition injected and the injection speed, but a hydrogel polymer having a weight average particle size of 2 to 50 mm is usually obtained.

[0066] In addition, when photopolymerization is performed in a reactor equipped with a movable conveyor belt as described above, the form of the hydrogel polymer obtained may be a hydrogel polymer on a sheet having the width of the belt. In this case, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition injected, and it is preferable to supply the monomer composition so that a polymer on a sheet having a thickness of about 0.5 to about 5 cm is obtained. If the monomer composition is supplied so that the thickness of the polymer on the sheet is too thin, the production efficiency is low, which is undesirable, and if the thickness of the polymer on the sheet exceeds 5 cm, the polymerization reaction may not occur evenly throughout the entire thickness due to the excessively thick thickness.

[0067] Meanwhile, in order to improve the absorption rate of the superabsorbent resin, a foaming agent capable of introducing a pore structure into the superabsorbent resin during cross-linking polymerization of the monomer composition may be further used. As such a foaming agent, any compound capable of generating foam during the polymerization step known in the art may be used without limitation, and for example, a carbonate-based foaming agent or an encapsulated foaming agent may be used.

[0068] As the carbonate-based foaming agent, for example, one or more selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate may be used.

[0069] Specifically, the carbonate-based foaming agent may be used in an amount of 0.005 to 1 part by weight based on 100 parts by weight of the acrylic acid-based monomer. If the content of the foaming agent is less than 0.005 part by weight, the role of the foaming agent may be insignificant, and if the content of the foaming agent is more than 1 part by weight, the number of pores in the crosslinked polymer is excessively large, so that the gel strength of the produced superabsorbent resin is reduced and the density is reduced, which may cause problems in distribution and storage.

[0070] The encapsulated foaming agent may be a thermally expandable microcapsule foaming agent having a core-shell structure. More specifically, the encapsulated foaming agent has a core-shell structure including a core containing a hydrocarbon and a shell made of a thermoplastic resin formed on the core. Specifically, the hydrocarbon constituting the core is easily vaporized by heat into liquid hydrocarbon having a low boiling point. Therefore, when heat is applied to the encapsulated foaming agent, the thermoplastic resin constituting the shell softens and the liquid hydrocarbon in the core vaporizes, increasing the pressure inside the capsule and expanding the agent, thereby forming bubbles larger than the existing size.

[0071] The hydrocarbon constituting the core of the encapsulated blowing agent may be one or more selected from the group consisting of n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane, n-hexane, iso-hexane, cyclohexane, n-heptane, iso-heptane, cycloheptane, n-octane, iso-octane and cyclooctane. Among these, hydrocarbons having 3 to 5 carbon atoms (n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane) are suitable for forming pores of the above-mentioned size, and iso-butane is the most suitable.

[0072] The thermoplastic resin constituting the shell of the encapsulated foaming agent may be a polymer formed from one or more monomers selected from the group consisting of (meth)acrylate compounds, (meth)acrylonitrile compounds, aromatic vinyl compounds, vinyl acetate compounds, and vinyl halide compounds. Among these, a copolymer of (meth)acrylate and (meth)acrylonitrile is most suitable for forming pores of the above-mentioned size.

[0073] In addition, such an encapsulated foaming agent may have a structure including a core containing a hydrocarbon and a shell formed of a thermoplastic resin surrounding the core, have an average diameter of 5 to 30 μm before expansion, and have a maximum expansion ratio in air of 5 to 15 times.

[0074] The encapsulated foaming agent may be used in an amount of 0.005 to 1 part by weight based on 100 parts by weight of the acrylic acid monomer. If the content of the foaming agent is less than 0.005 part by weight, the foaming agent may not function as a foaming agent, and if the content of the foaming agent is more than 1 part by weight, the crosslinked polymer may have too many pores, resulting in a decrease in gel strength and a decrease in density of the produced superabsorbent resin, which may cause problems in distribution and storage.

[0075] In addition, in step 2, a surfactant that is generally used as a foam stabilizer may be added together with the carbonate foaming agent. Examples of such surfactants include alkyl sulfate compounds and polyoxyethylene alkyl ether compounds. Examples of the alkyl sulfate compounds include sodium dodecyl sulfate, ammonium lauryl sulfate, sodium laurylether sulfate, and sodium myreth sulfate, and examples of the polyoxyethylene alkyl ether compounds include polyoxyethylene lauryl ether. In this case, the alkyl sulfate compounds are anionic surfactants, and the polyoxyethylene alkyl ether compounds are nonionic surfactants.

[0076] The water content of the hydrogel polymer obtained by this method may be about 40 to about 80% by weight. Meanwhile, throughout this specification, the "water content" refers to the water content relative to the total weight of the polymer, and means the weight of the polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to the evaporation of water in the polymer during the process of drying the polymer by increasing the temperature through infrared heating. Here, the drying conditions are a method of increasing the temperature from room temperature to about 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including a 5-minute temperature increase step, and the water content is measured.

[0077] (Step 3) The hydrous gel polymer is then dried, ground and classified to form a base resin.

[0078] Meanwhile, before drying the hydrogel polymer, a step of coarsely pulverizing the hydrogel polymer may be further performed. The type of pulverizer used for the pulverization is not particularly limited, and specifically, may include any one selected from the group of pulverizing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter.

[0079] The coarse pulverization may be performed so that the hydrogel polymer has a particle size of about 1 mm to about 10 mm. It is technically difficult to pulverize the hydrogel polymer to a particle size of less than 1 mm due to the high water content of the hydrogel polymer, and the pulverized particles may aggregate with each other. On the other hand, when the hydrogel polymer is pulverized to a particle size of more than 10 mm, the effect of increasing the efficiency of the subsequent drying step is minimal.

[0080] The drying temperature of the drying step may be about 150 to about 250° C. If the drying temperature is less than 150° C., the drying time may be too long, which may result in a deterioration in the properties of the superabsorbent polymer formed at the end, and if the drying temperature is more than 250° C., only the polymer surface may be dried excessively, which may result in fine powder being generated in the subsequent pulverization process, which may result in a deterioration in the properties of the superabsorbent polymer formed at the end. Therefore, the drying may be preferably performed at a temperature of about 150 to about 200° C., more preferably at a temperature of about 170 to about 200° C.

[0081] Meanwhile, the drying time may be about 20 to about 90 minutes in consideration of process efficiency, but is not limited thereto.

[0082] The drying method of the drying step can be selected and used without any limitation as long as it is a method usually used in the drying process of hydrogel polymers. Specifically, the drying step may be performed by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after such a drying step may be about 5 to about 10% by weight.

[0083] Next, the dried polymer obtained through the drying step is pulverized. At this time, the pulverization may be performed to obtain a powder form containing particles having a particle size of about 150 to about 850 μm. The pulverizer used to pulverize to such a particle size may be, for example, a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill, but is not limited to the above examples.

[0084] After the pulverization step, the base resin obtained after pulverization is classified according to particle size in order to control the physical properties of the superabsorbent resin powder to be the final product. Preferably, polymers having a particle size of about 150 to about 850 μm are classified, and only the base resin having such a particle size may be subjected to the surface crosslinking reaction step. In this case, the particle size may be measured according to the EDANA WSP 220.3 method of the European Disposables and Nonwovens Association (EDANA) standard.

[0085] (Step 4) Next, a surface cross-linking step is carried out in the presence of a surface cross-linking solution containing a surface cross-linking agent, water, and an organic solvent having a boiling point of less than 90° C. to form a surface cross-linked layer on the surface of the base resin.

[0086] Through the above steps, a superabsorbent resin is produced in which a surface cross-linked layer is formed on at least a portion of the surface of the base resin, more specifically, on at least a portion of the surface of each of the base resin particles.

[0087] The surface cross-linking is a step that increases the cross-linking density near the surface of the base resin particles relative to the cross-linking density inside the particles. Generally, the surface cross-linking agent is applied to the surface of the superabsorbent resin particles. Thus, the reaction occurs on the surface of the base resin particles, which improves the cross-linking on the surface of the particles while leaving the inside of the particles substantially unaffected. Thus, the surface cross-linked superabsorbent resin particles have a higher degree of cross-linking near the surface than inside.

[0088] The surface cross-linking agent may be an epoxy-based surface cross-linking agent containing two or more epoxy groups in the molecule. For example, the surface cross-linking agent may be one or more selected from the group consisting of ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether (number of ethylene glycol repeating units: 2 to 22), propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether (number of propylene glycol repeating units: 2 to 66), glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether (number of glycerol repeating units: 2 to 3), and sorbitol polyglycidyl ether.

[0089] According to one embodiment, the surface cross-linking agent may be the same as the internal cross-linking agent. For example, the surface cross-linking agent may include ethylene glycol diglycidyl ether. The ethylene glycol diglycidyl ether is highly water-soluble and has two epoxy groups, so that the surface reaction can be easily carried out even at a relatively low temperature.

[0090] The content of the surface cross-linking agent may be appropriately selected depending on the type of the surface cross-linking agent to be added and the reaction conditions, and may be about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.03 to about 2 parts by weight, based on 100 parts by weight of the base resin. If the content of the surface cross-linking agent is too small, the surface cross-linking reaction hardly occurs, and if the content exceeds 5 parts by weight based on 100 parts by weight of the base resin, there is a possibility that the absorption properties such as water retention ability will decrease due to the excessive progress of the surface cross-linking reaction.

[0091] In the present invention, the surface crosslinking agent is applied to the base resin in the form of a surface crosslinking solution dissolved in a solvent. When the surface crosslinking agent is added in the form of a solution, the surface crosslinking agent can be more uniformly dispersed in the base resin, which is preferable.

[0092] In particular, in the present invention, water and an organic solvent having a boiling point of less than 90°C are used as a solvent for the surface crosslinking solution, and at this time, the weight ratio of water / organic solvent is set to be 1.0 or more and less than 3.0, thereby increasing the application efficiency of the surface crosslinking solution and producing a superabsorbent resin that simultaneously satisfies the above-mentioned physical properties i) to v).

[0093] When an organic solvent having a boiling point of less than 90°C (hereinafter referred to as "organic solvent") is used as a co-solvent together with water as described above, the organic solvent having a boiling point lower than that of water is first evaporated after the surface crosslinking solution is applied to the surface of the base resin, and then both the water and the surface crosslinking agent can penetrate deeply into the inside of the base resin, and a deeper and more uniform surface crosslinked layer can be formed.

[0094] As the organic solvent, for example, one or more selected from the group consisting of methanol, ethanol, isopropanol, acetone, and ethyl acetate may be used.

[0095] Preferably, the organic solvent may be ethanol and / or isopropanol, more preferably isopropanol.

[0096] Isopropanol is less toxic and odorous, and a surface crosslinking solution containing isopropanol is preferable because it can be absorbed at an appropriate rate into the surface of the base resin. That is, if the surface crosslinking solution is absorbed too quickly into the surface of the base resin, the solution is difficult to apply evenly, but when isopropanol is used, the surface crosslinking solution is absorbed into the base resin at an appropriate rate, so that it can be applied more evenly onto the surface of the base resin.

[0097] In this case, the weight ratio of water / organic solvent in the surface crosslinking solution is set to be 1.0 or more and less than 3.0, and the content of the organic solvent in the total weight of the surface crosslinking solution is set to be 24 weight% or more, thereby increasing the application efficiency of the surface crosslinking solution, and a superabsorbent resin that simultaneously satisfies the above-mentioned physical properties i) to v) can be produced.

[0098] If the weight ratio of water / organic solvent is more than 3.0, the surface cross-linking solution cannot be uniformly applied to the base resin. Therefore, in this case, the surface cross-linking degree of each base resin particle is different from each other, and not only uniform absorption properties cannot be achieved, but also excessive waste, which is an aggregate formed by the base resin solidifying with a particle size exceeding 850 μm, is generated during the surface cross-linking process, which may cause problems in productivity as the process does not proceed smoothly.

[0099] Therefore, the weight ratio of water / organic solvent of the surface cross-linking solution may be 2.9 or less, or 2.8 or less, or 2.7 or less, and 1.2 or more, or 1.7 or more, or 2.3 or more. If the ratio of water in the solvent of the surface cross-linking solution is too low, the surface cross-linking layer is generated thinly, and when the superabsorbent resin swells, cracks may occur on the surface. In addition, if the ratio of organic solvent in the solvent of the surface cross-linking solution is too high, a large amount of organic solvent may remain in the superabsorbent resin, which is not preferable.

[0100] In addition, the content of the organic solvent in the total weight of the surface crosslinking solution may be 24% by weight or more, or 25% by weight or more, or 25.9% by weight or more, and 40% by weight or less, or 35% by weight or less, or 30% by weight or less. If the content of the organic solvent is less than 24% by weight, the application efficiency of the surface crosslinking solution may decrease, and if it exceeds 40% by weight, the organic solvent may remain in the produced superabsorbent resin, so it is preferable to satisfy the above range.

[0101] Meanwhile, the surface cross-linking solution may further contain an additive for further increasing the application efficiency of the solution. For example, the additive may be one or more glycol compounds selected from the group consisting of propylene glycol, dipropylene glycol, tripropylene glycol, and glycerin; and / or a polycarboxylic acid copolymer. Preferably, the additive may be propylene glycol and a polycarboxylic acid copolymer. Propylene glycol and a polycarboxylic acid copolymer are non-toxic and do not cause unpleasant odors after production, so they can be used more preferably.

[0102] The additive may be used in a content of 15 wt % or less, or 12 wt % or less, and 1 wt % or more, or 2 wt % or more, or 3 wt % or more, based on the total weight of the surface crosslinking solution.

[0103] Specifically, the glycol compound may be used in an amount of 1% by weight or more, or 2% by weight or more, or 3% by weight or more, and 10% by weight or less, or 9% by weight or less, in the surface cross-linking solution. The polycarboxylic acid copolymer may be used in an amount of 0.05% by weight or more, or 0.1% by weight or more, and 1% by weight or less, or 0.5% by weight or less, in the surface cross-linking solution.

[0104] In addition, in the surface cross-linking solution, the density of the surface cross-linking agent represented by the following formula 3 is preferably 1.0 or more and less than 17.0.

[0105] [Formula 3] Density of surface cross-linking agent = (weight of surface cross-linking agent) / (weight of water) x 1,000

[0106] When the density of the surface cross-linking agent is less than 1.0, the amount of the surface cross-linking agent is insufficient, so that it may be difficult to achieve a suitable degree of surface cross-linking. Also, when the density of the surface cross-linking agent is 17.0 or more, the cross-linking density is excessively high, so that when the superabsorbent resin swells to the maximum, there may be a problem that cracks occur on the surface cross-linked surface, and the internal base resin is exposed. Therefore, the density of the surface cross-linking agent is preferably in the above range, and more preferably is 2.0 or more, or 3.0 or more, or 4.0 or more, and 15.0 or less, or 12.0 or less, or 9.0 or less, or 6.0 or less.

[0107] Meanwhile, the surface cross-linking solution may further contain one or more selected from the group consisting of a polyvalent metal salt, for example, an aluminum salt, more specifically, an aluminum sulfate salt, a potassium salt, an ammonium salt, a sodium salt, and a hydrochloride salt.

[0108] When such a polyvalent metal salt is further used, the liquid permeability of the highly water-absorbent resin can be further improved. For example, the polyvalent metal salt may be used in an amount of 0.01 to 4 parts by weight based on 100 parts by weight of the base resin.

[0109] The temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. In this case, the type of heat medium that can be used may be a heated fluid such as steam, hot air, or hot oil, but the present invention is not limited to these, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, the heat source to be directly supplied includes heating through electricity and heating through gas, but the present invention is not limited to the above-mentioned examples.

[0110] The surface cross-linking reaction may be carried out under normal pressure (760±50 torr), and the reaction temperature may be 100° C. or more, or 110° C. or more, or 120° C. or more, and less than 160° C., or less than 150° C., or less than 140° C., or less than 130° C. If the reaction temperature is less than 100° C., the reaction may not proceed smoothly, and if the reaction temperature is 160° C. or more, the glycol compound used to increase the application efficiency of the surface cross-linking solution may cause a cross-linking reaction, making it impossible to achieve the intended effect.

[0111] When the surface cross-linking step is performed using a surface cross-linking solution satisfying the weight ratio of water / organic solvent as described above, the surface cross-linking solution is evenly applied to the base resin at an appropriate concentration, so that the base resins do not aggregate with each other and the surfaces of each base resin can be cross-linked to a uniform degree. As a result, the amount of waste generated after the surface cross-linking step may be 4.0 wt% or less, or 3.0 wt% or less, or 2.8 wt% or less.

[0112] On the other hand, after forming a surface cross-linked layer on the surface of the base resin as described above, an inorganic substance can be further added.

[0113] The inorganic material may be, for example, one or more selected from the group consisting of silica, clay, alumina, a silica-alumina composite material, and titania, and preferably, silica may be used.

[0114] Such inorganic substances may be used in an amount of 0.01 parts by weight or more, or 0.05 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, or 3 parts by weight or less, or 1 part by weight or less, relative to 100 parts by weight of the superabsorbent resin.

[0115] Meanwhile, in order to control the physical properties of the superabsorbent polymer to be manufactured as a final product, a step of classifying the superabsorbent polymer obtained after the surface cross-linking step according to particle size may be additionally performed. Preferably, polymers having a particle size of about 150 to about 850 μm are classified, and only the superabsorbent polymer having such a particle size can be used as the final product.

[0116] Through the above-mentioned preparation method, it is possible to provide a superabsorbent resin having a small difference between the internal crosslink density and the surface crosslink density. Since the surface of such a superabsorbent resin expands well when absorbing water, it is possible to simultaneously improve the centrifugal water retention capacity and the pressure absorption capacity, and thus to provide a superabsorbent resin having a high absorption speed. As a result, the superabsorbent resin can simultaneously satisfy the above-mentioned physical properties of i) centrifugal water retention capacity, ii) pressure absorption capacity, iii) absorption speed, iv) 1-minute tap water absorption capacity, and v) rewetting characteristics.

[0117] The present invention will be described in more detail with reference to the following examples. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.

[0118] <Example> Example 1 (Step 1) 100 g of acrylic acid, 0.001 g of PEGDA400 (polyethylene glycol diacrylate, Mw=400) as an internal crosslinking agent, 0.18 g of ethylene glycol diglycidyl ether (EJ1030s), 0.008 g of diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide (I-819) as a photopolymerization initiator, and 0.12 g of sodium persulfate (SPS) as a thermal polymerization initiator were added and dissolved in a 3 L glass container equipped with a stirrer and a thermometer, and then 188 g of 22% sodium hydroxide solution was added to prepare a monomer composition (neutralization degree: 75 mol%; solid content: 43 wt%).

[0119] (Step 2) 0.02 g of a 28% aqueous solution of sodium dodecyl sulfate (SDS) and 0.18 g of an encapsulated foaming agent F-36D (manufactured by Matsumoto Co., Ltd.) were added to the monomer composition. The monomer composition was then fed at a rate of 500 to 2000 mL / min onto a conveyor belt, 10 cm wide and 2 m long, rotating at a speed of 50 cm / min. The monomer composition was then fed at a rate of 10 mW / cm 2 The polymerization reaction was carried out for 60 seconds by irradiating the solution with ultraviolet light having an intensity of 100 nm to obtain a sheet-shaped hydrogel polymer having a water content of 55% by weight.

[0120] (Step 3) Next, 0.032 parts by weight of sodium metabisulfite (SMBS; Na) was added to 100 parts by weight of the acrylic acid monomer. 2 S 2 O 5 The aqueous sodium metabisulfite solution was sprayed onto a hydrogel polymer cut into a size of about 5 cm x 5 cm, which was then put into a meat chopper and chopped into hydrogel particle crumbs having sizes of 1 mm to 10 mm.

[0121] The crumb was then dried in an oven with an adjustable airflow direction. Hot air of 190°C or higher was blown from bottom to top for 15 minutes, then from top to bottom for another 15 minutes to dry evenly, so that the moisture content of the dried material after drying was 2% or less. After drying, the crumb was pulverized in a pulverizer and classified to prepare a base resin (BR) by selecting a size of 150 to 850 μm.

[0122] (Step 4) Based on 100 g of the base resin, 7 g of water, 3 g of isopropanol (IPA) as an organic solvent, 0.035 g of ethylene glycol diglycidyl ether (EJ1030s) as a surface crosslinking agent, 1.0 g of propylene glycol (PG) as an additive, 0.05 g of a polycarboxylic acid copolymer (a copolymer of methoxypolyethylene glycol monomethacrylate and methacrylic acid, GK, Mw=40,000), and 0.04 g of aluminum sulfate (Al-S) were mixed to prepare a surface crosslinking solution.

[0123] The surface cross-linking solution was sprayed and mixed into 100 g of the obtained base resin, and the mixture was placed in a vessel consisting of a stirrer and a double jacket, and a surface cross-linking reaction was carried out at 125° C. for 35 minutes. The surface-treated powder was then classified using a standard mesh sieve according to ASTM standards to obtain a superabsorbent resin powder having a particle size of 150 to 850 μm. Then, 0.15 g of fumed silica (AEROSIL® 200) was added and mixed with 100 parts by weight of the obtained resin powder.

[0124] Example 2, Example 4, Comparative Example 1, Comparative Example 4, and Comparative Example 5 In step 4, a superabsorbent resin was produced in the same manner as in Example 1, except that the water, isopropanol (IPA), propylene glycol (PG), and ethylene glycol diglycidyl ether (EJ1030s) contained in the surface crosslinking solution were used in the amounts shown in Table 1 below.

[0125] Example 3, Comparative Example 2, and Comparative Example 3 A base resin was prepared in the same manner as in steps 1 to 3 of Example 1, except that 0.16 g of ethylene glycol diglycidyl ether (EJ1030s) was used in the preparation of the monomer composition in step 1.

[0126] Thereafter, a superabsorbent resin was produced in the same manner as in step 4 of Example 1, except that the water, isopropanol (IPA), propylene glycol (PG), and ethylene glycol diglycidyl ether (EJ1030s) contained in the surface crosslinking solution were used in the amounts shown in Table 1 below.

[0127] In Table 1 below, the content of each component is expressed as weight (g) per 100 g of base resin.

[0128] [Table 1]

[0129] [Table 2]

[0130] Experimental example: Measurement of the physical properties of superabsorbent resin The properties of the base resins and superabsorbent resins produced in the above examples and comparative examples were evaluated by the following methods, and are shown in Tables 2 and 3 below, respectively. Table 2 shows the properties of each base resin, and Table 3 shows the properties of the superabsorbent resin obtained after the surface treatment step. The properties of the superabsorbent resins were measured without any additional classification after production, and the centrifugation retention capacity (CRC) and absorption speed (vortex time) of the base resins were measured using the fraction classified using a #40-50 sieve (particle size 300-425 μm).

[0131] Unless otherwise stated, all the processes for the evaluation of the physical properties below were carried out in a constant temperature and humidity room (23±0.5℃, relative humidity 45±0.5%), and the measurement data was the average value of three measurements to prevent measurement errors. In addition, the physiological saline or salt water used in the evaluation of the physical properties below refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution.

[0132] (1)Centrifuge Retention Capacity (CRC) The water retention capacity of each resin was measured by the no-load absorbency according to EDA WSP 241.3.

[0133] Specifically, the highly water-absorbent resin W 0 (g) (about 0.2 g) was uniformly placed in a nonwoven envelope, sealed, and then immersed in physiological saline at room temperature. After 30 minutes, the envelope was centrifuged at 250 G for 3 minutes to remove water, and the mass of the envelope W 2 The mass W (g) was measured after the same procedure was performed without using the resin. 1 The mass (g) was measured. The CRC (g / g) was calculated using the obtained masses according to the following formula:

[0134] [Formula 2] CRC(g / g) = {[W 2 (g)-W 1 (g)] / W 0 (g)}-1

[0135] (2) Absorbtion Under Pressure (AUP) The 0.3 psi pressure absorbency of each resin was measured by EDANA method WSP 242.3.

[0136] Specifically, a 400 mesh stainless steel iron net was attached to the bottom of a plastic cylinder with an inner diameter of 60 mm. The superabsorbent resin W was placed on the iron net under conditions of room temperature and 50% humidity. 3 (g) (0.90g) was evenly spread on the cylinder, and a piston capable of applying a load of 0.3 psi evenly was placed on top of it. The piston had an outer diameter slightly smaller than 60 mm, had no gap with the inner wall of the cylinder, and was designed so that its vertical movement was not hindered. At this time, the weight W 4 (g) was measured.

[0137] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a petroleum dish with a diameter of 150 mm, and physiological saline was poured so that it was flush with the top surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper and allowed to absorb the liquid under load for one hour. After one hour, the measuring device was lifted up and its weight W 5 (g) was measured.

[0138] Using the obtained masses, the pressurized absorbency (g / g) was calculated according to the following formula.

[0139] [Formula 3] AUP(g / g) = [W 5 (g)-W 4 (g)] / W 3 (g)

[0140] (3) Effective Absorption Capacity (EFFC, 0.3 psi) The effective absorbency (EFFC, 0.3 psi) was calculated from the CRC and 0.3 psi AUP of each superabsorbent polymer calculated above according to the following Equation 1.

[0141] [Formula 1] Effective Absorbent Capacity (EFFC) = {Water Retention Capacity (CRC) + Absorbent Capacity under 0.3 psi Pressure (AUP)} / 2

[0142] (4) Absorption speed (Vortex time) The absorption speed (vortex time) of the superabsorbent resins of the above Examples and Comparative Examples was measured in accordance with the Japanese standard method (JIS K 7224) as follows.

[0143] (i) First, 50 mL of saline was poured into a 100 mL beaker with a flat bottom using a 100 mL mass cylinder. (ii) Next, the beaker was placed in the center of a magnetic stirrer, and then a magnetic bar (diameter 8 mm, length 30 mm) was placed in the beaker. (iii) Then, the stirrer was operated so that the magnetic bar was stirring at 600 rpm, and the lowest point of the vortex generated by the stirring was placed on the magnetic bar. (iv) After confirming that the temperature of the salt water in the beaker had reached 24.0°C, 2±0.01 g of a superabsorbent resin sample (particle size 300 to 600 μm) was added while simultaneously starting a stopwatch. The time until the vortex disappeared and the liquid surface became completely horizontal was measured in seconds, and this was regarded as the absorption rate.

[0144] (5) Rewetting with pressurized salt water for 2 hours (i) 4 g of superabsorbent resin was evenly spread on a 130 mm diameter petroleum dish, 100 g of physiological saline was poured in, and the dish was covered and left to swell for 120 minutes. Separately, 20 sheets of filter paper (manufacturer: Whatman, catalog No. 1004-110, pore size 20-25 μm, diameter 110 mm) with a weight of W 6 (g) was measured. (ii) After 120 minutes had elapsed, 20 sheets of the filter paper were stacked on top of the superabsorbent resin, and a pressure of 0.75 psi was applied to the resin by a weight of 110 mm in diameter and 5 kg for 5 minutes. (iii) After 5 minutes, the weight W of the filter paper that absorbed the saline solution 7 (g) was measured. (iv) Using the obtained masses, the amount of saline absorbed by the filter paper (rewet amount, g) was calculated according to the following formula:

[0145] [Formula 4] Rewetting amount (g) = W 7 (g)-W 6 (g)

[0146] (6) 1min Tap Water Free Absorbency The one-minute tap water absorbency of the superabsorbent resins of the Examples and Comparative Examples was measured by the following method.

[0147] (i) First, 1 g of a superabsorbent resin was placed in a tea bag measuring 15 cm in width and 30 cm in length, and the tea bag was immersed in 2 L of tap water and then allowed to swell for 1 minute. (ii) After that, the tea bag containing the swollen superabsorbent polymer was lifted out of the tap water, and after one minute had passed, the weights of the tea bag from which the tap water had been drained and the superabsorbent polymer were both measured, and the weight of the empty tea bag was subtracted to obtain the one-minute tap water absorbency.

[0148] The tap water used had an electrical conductivity of 170 to 180 μS / cm when measured using an Orion Star A222 (manufactured by Thermo Scientific).

[0149] [Table 3]

[0150] [Table 4]

[0151] Referring to Table 4 above, it can be seen that the superabsorbent resins of Examples 1 to 4 exhibit a fast absorption rate, as well as excellent centrifugal water retention capacity and pressure absorption capacity, and have improved rewetting properties due to a small rewetting amount, and are also excellent in one-minute tap water absorption capacity.

[0152] Such superabsorbent polymers, which are excellent in all of the centrifugal water retention capacity, absorption speed, EFFC and 1-minute tap water absorption capacity, can rapidly absorb liquid and the absorbed liquid does not seep out or leak even under pressure, and are therefore used in diapers and the like, where they can exhibit excellent absorption performance and wearing comfort.

Claims

1. i) the centrifugal water retention capacity is 30 g / g or more; ii) the effective absorbent capacity (EFFC, 0.3 psi) calculated by the following formula 1 is greater than 29.5 g / g; iii) the absorption rate by the vortex method is less than 37 seconds; iv) when 1 g of the superabsorbent polymer is immersed in 2 L of tap water and allowed to swell for 1 minute, the 1-minute tap water absorbency, defined as the weight of water absorbed by the superabsorbent polymer for 1 minute, exceeds 115 g; v) A superabsorbent resin in which 4 g of the superabsorbent resin is immersed in 100 g of a 0.9 wt % sodium chloride aqueous solution to swell for 120 minutes, a filter paper is placed on the superabsorbent resin, and a pressure of 0.75 psi is applied for 5 minutes. The rewetting property (rewetted with pressurized salt water for 2 hours) is defined as the weight of water that seeps out from the superabsorbent resin to the filter paper, and is less than 3.7 g. [Formula 1] Effective Absorbent Capacity (EFFC, 0.3 psi) = {Centrifugation Capacity (CRC) + Absorbent Capacity under Pressure (AUP) at 0.3 psi} / 2

2. i) the centrifugal water retention capacity is 32 g / g to 40 g / g; ii) an effective absorbent capacity (EFFC) of 30 g / g to 40 g / g; iii) The highly water-absorbent resin according to claim 1, which has an absorption speed of 20 to 30 seconds as measured by a vortex method.

3. v) The highly water-absorbent resin according to claim 1 or 2, having a pressurized salt water 2-hour rewet value of 3.4 g or less.

4. Providing a monomer composition including an acrylic acid monomer having at least a partially neutralized acid group, an internal crosslinking agent, and a polymerization initiator; cross-linking the monomer composition to form a hydrogel polymer; drying, grinding and classifying the hydrous gel polymer to form a base resin; A surface cross-linking step of forming a surface cross-linked layer on the surface of the base resin in the presence of a surface cross-linking solution containing a surface cross-linking agent, water, and an organic solvent having a boiling point of less than 90° C.; The weight ratio of water / organic solvent in the surface crosslinking solution is 1.0 or more and less than 3.0; The method for producing a highly water-absorbent resin according to claim 1, wherein the content of the organic solvent in the surface cross-linking solution is 24% by weight or more.

5. 5. The method for producing a highly water-absorbent resin according to claim 4, wherein the content of the organic solvent in the surface cross-linking solution is 25% by weight to 30% by weight.

6. 6. The method for producing a highly water-absorbent resin according to claim 4, wherein the surface cross-linking solution contains a surface cross-linking agent having a density of 1.0 or more and less than 17.0, the density being represented by the following formula 3: [Formula 3] Density of surface cross-linking agent=(weight of surface cross-linking agent) / (weight of water)×1,000

7. The method for producing a highly water-absorbent resin according to claim 4, wherein the organic solvent is at least one selected from the group consisting of methanol, ethanol, isopropanol, acetone, and ethyl acetate.

8. 5. The method for producing a highly water-absorbent resin according to claim 4, wherein after the surface cross-linking step, the amount of scraps generated by the base resin having a particle size exceeding 850 μm is less than 4.0% by weight.

9. The method for producing a superabsorbent polymer according to claim 4, further comprising the step of adding and mixing one or more inorganic substances selected from the group consisting of silica, clay, alumina, silica-alumina composites, and titania to the superabsorbent polymer after the surface cross-linking step.

10. 10. The method for producing a highly absorbent polymer according to claim 9, wherein the inorganic substance is added in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the highly absorbent polymer.

Citation Information

Patent Citations

  • Highly water-absorbent resin and method for producing the same

    JP2021505704A

  • Highly water-absorbent resin and method for producing the same

    JP2022514512A

  • KR20190069101A

  • KR20220049961A